Tailoring Silk Sericin Grafting: Comparing One‐Step and Two‐Step Approaches for PNIPAM/PAMPS Block Nanoparticles - Ionut‐Cristian Radu; Derniza‐Elena Cozorici; Erika Blanzeanu; Andreea Vadureanu; Cristina Stavarache; Eugenia Tanasa; Horia Iovu; Catalin Zaharia (Macromolecular Materials and Engineering)
Abstract Structurally defined, protein‐grafted nanoparticles are widely used in various biomedical applications, particularly as intelligent nanocarriers for drug delivery. The integration of synthetic polymers with natural proteins such as silk sericin enhances the functionality and stability of these nanocarriers, making them suitable for targeted and controlled drug release. In this context, an optimized grafting procedure for silk sericin is presented, employing a protein macroinitiator and atom transfer radical polymerization (ATRP). This study aims to elucidate the significance of the grafting process in tailoring the structure of sericin through the chemistry of synthetic grafts. The grafting procedure uses block copolymers of N‐isopropylacrylamide (NIPAM) and 2‐acrylamido‐2‐methylpropanesulfonic acid (AMPS), such as Poly‐(AMPS‐block‐NIPAM)/Poly‐(NIPAM‐block‐AMPS). The procedure employs both one‐step and two‐step synthesis methods to produce a well‐defined, biofunctionalized sericin. Subsequently, sericin‐based nanoparticles are prepared, demonstrating the significance of the optimized procedure. The synthesized products undergo structural analysis using H‐NMR, FTIR‐ATR, XPS, DLS, and zeta potential measurements. In addition, their thermal behavior is assessed using differential scanning calorimetry. To further investigate the prepared nanoparticles, SEM and DLS analyses are conducted. Through synthesis optimization, position and length of each synthetic block is precisely determined, significantly influencing properties of the grafted products and characteristics of the resulting nanoparticles.